Uptake of Polyelectrolyte Functionalized Upconversion Nanoparticles by Tau-Aggregated Neuron Cells - Yo Han Song; Ranjit De; Kang Taek Lee (MDPI AG, 2021)
Tauopathy is the aggregation phenomenon of tau proteins and associated with neurodegenerative diseases. It metastasizes via the transfer of tau aggregates to adjacent neuron cells; however, the mechanism has not yet been fully understood. Moreover, if the materials used for designing drug delivery system to treat such neurodegenerative diseases do not undergo biodegradation or exocytosis but remains in cells or tissues, they raise concerns about their possible negative impacts. In this study, the uptake and delivery mechanisms of nano-sized carriers in tau aggregated neuron cells were investigated employing polyelectrolyte-functionalized upconversion nanoparticles (UCNPs) of diameter ~100 nm. Investigation through bioimaging was carried out by irradiating the particles with near-infrared light. Here, forskolin and okadaic acid were employed to induce tau aggregation into healthy neuron cells. It was noticed that the tau-aggregated neuron cells, when treated with relatively large sized UCNPs, showed uptake efficiency similar to that of normal neuron cells however their intracellular transport and exocytosis were impacted, and most of the carriers remained accumulated around lysosome. This demonstrates that metastasis mechanisms of tauopathy can get influenced by the size of carriers and are to be considered during their pharmacokinetic studies which is often not addressed in many drug delivery studies.